Information Behaviour of Medical Personnel in University College Hospital, Ibadan (Lead City International Journal of Library, Information & Communication Sciences, 2025)
This study examines the information-seeking patterns, preferred sources, challenges, and role of the library in supporting the medical staff at University College Hospital (UCH), Ibadan. Data were gathered through a structured questionnaire administered to doctors, nurses, and other healthcare professionals. Findings indicate that while digital resources are increasingly utilized, a strong reliance on traditional print materials remains. Barriers such as time constraints, inadequate ICT skills, and access limitations were identified. The study suggests strategies for libraries to enhance information accessibility and literacy among medical personnel. Results reveal that 57.7% of respondents seek information daily, primarily for patient care, research, and professional development. The internet and online databases were the most commonly used sources, though only a fraction of respondents found them highly reliable. The UCH Library was significantly underutilized, with many citing lack of awareness, limited resources, and insufficient training as major factors. Despite these challenges, respondents demonstrated a strong motivation to engage in information-seeking, underscoring the need for improved infrastructure, staff support, and targeted information literacy programs to enhance the library's role in clinical decision-making.